Mapping Invasion Potential of the Pest from Central Asia, Trypophloeus klimeschi (Coleoptera: Curculionidae: Scolytinae), in the Shelter Forests of Northwest China - Hang Ning; Ming Tang; Hui Chen (Insects, 2021)
Temperature and precipitation are the two main factors constraining the current distribution of Trypophloeus klimeschi. Currently, T. klimeschi is mainly distributed in South Xinjiang, where it occurs between the southern edge of the Tianshan Mountains and northern edge of the Tarim Basin. In addition, Dunhuang in northern Gansu also provide suitable habitats for this bark beetle. Two other potential areas for this species are in or near the cities of Alaer and Korla. Under future climate scenarios, its total suitable area is projected to increase markedly over time. Among the climate scenarios, the distribution expanded the most under the maximum greenhouse gas emission scenario (representative concentration pathway (RCP) 8.5). Jiuquan in Gansu is projected to become a suitable area in the 2030s. Subsequently, T. klimeschi is expected to enter western Inner Mongolia along the Hexi Corridor in the 2050s. In southeastern Xinjiang, however, the suitable area in northern Ruoqiang and most areas of Korla may decrease. By the 2050s, it is large enough to pose substantial challenges for forest managers across northern China. Our findings provide information that can be used to monitor T. klimeschi populations, host health, and the impact of climate change, shedding light on the effectiveness of management responses.